2012
DOI: 10.1155/2012/503241
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Cruciferous Plants in Humans: A Systematic Review

Abstract: Some cruciferous plants may serve as preventive treatments for several medical conditions; our objective was to systematically investigate their safety in humans. Four electronic databases were searched, and, of 10,831 references identified, 50 were included. Data were extracted by two independent reviewers, whereafter the association between interventions and adverse events was assessed. Adverse events in 53 subjects were identified through clinical trials; of these, altered drug metabolism was rated as certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 69 publications
0
6
0
1
Order By: Relevance
“…However, because other organs do not accumulate isothiocyanates and cannot reach such high concentrations as the bladder, toxicity is a possibility when attempting to achieve high enough concentrations for chemopreventive effects in these organs. Overall cruciferous plants at usual intake appear to be safe in humans with the exception of allergies and with special precaution taken by those taking blood‐thinning medications such as Warfarin …”
Section: In Vitro and In Vivo Studies Of Isothiocyanates And Bladder mentioning
confidence: 99%
“…However, because other organs do not accumulate isothiocyanates and cannot reach such high concentrations as the bladder, toxicity is a possibility when attempting to achieve high enough concentrations for chemopreventive effects in these organs. Overall cruciferous plants at usual intake appear to be safe in humans with the exception of allergies and with special precaution taken by those taking blood‐thinning medications such as Warfarin …”
Section: In Vitro and In Vivo Studies Of Isothiocyanates And Bladder mentioning
confidence: 99%
“…estimated daily intake), origin of the food, modes of production and known differences from other food items that could be used for comparison, Eventually, toxicity testing in animal studies would be performed (see Howlett et al 2003 for more details). Thus, even though according to a systematic literature review Brassicaceae are generally considered safe for humans (Scott et al 2012), it would be a long way before leaves of Zn hyperaccumulating plants or powder derived from such leaves could be adopted as food ingredients. The path would be much shorter if underutilized Brassicaceae or other vegetable crops can be identified that have a history of use as part of the diet anywhere in the world and show strong Zn accumulation in leaves below the hyperaccumulation range.…”
Section: Possible Practical Usages Of Zn Hyperaccumulators For Bioformentioning
confidence: 99%
“…To our knowledge, the effect of SF on the efficacy of bioreductive anticancer prodrugs, especially PR-104, has not been investigated previously. SF is bioavailable in the colon [ 4 ] and eating cruciferous plants seems to have a high margin of safety [ 57 ], suggesting the combination of SF with PR-104 may promote efficacy. Further studies to evaluate the robustness and selectivity of the response in vivo are warranted, but not trivial in a model organism because biotransformation of PR-104 has been shown to differ in humans vs. rodents, consistent with rodents not expressing a homolog of AKR1C3 [ 58 ].…”
Section: Discussionmentioning
confidence: 99%